True (--sort of) - Hannigan, Katherine (New York : Greenwillow Books, 2011)
For most of her eleven years, Delly has been in trouble without knowing why, until her little brother, R.B., and a strange, silent new friend, Ferris, help her find a way to be good--and happy--again.
3.8
3-6.
3-6
Keywords: Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Friendship -- Juvenile fiction; Human behavior -- Juvenile fiction; Schools -- Juvenile fiction; Selective mutism -- Juvenile fiction; Self-control -- Juvenile fiction; Behavior -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Friendship -- Fiction; Schools -- Fiction; Selective mutism -- Fiction; Self-control -- Fiction; Family life -- Fiction; Friendship -- Fiction; Human behavior -- Fiction; School stories; Selective mutism -- Fiction; Self-control -- Fiction; Siblings -- Fiction